2019
DOI: 10.1136/bmjopen-2018-023600
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of pregabalin in the management of neuropathic pain: a rapid review and meta-analysis of randomised clinical trials

Abstract: ObjectiveTo assess the benefits and harms of pregabalin in the management of neuropathic pain.DesignRapid review and meta-analysis of phase III, randomised, placebo-controlled trials.ParticipantsAdults aged 18 years and above with neuropathic pain defined according to the International Association for the Study of Pain criteria.InterventionsPregabalin or placebo.Primary and secondary outcome measuresOur primary outcomes were pain (as measured using validated scales) and adverse events. Our secondary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 58 publications
(31 reference statements)
4
65
0
6
Order By: Relevance
“…Following the PBS subsidy of pregabalin, we observed high rates of pregabalin initiation from 2013/14 to 2016/17 with only a slight drop in 2017/18. However, consistent with other studies, 7,17,18 we observed high rates of discontinuation which have been increasing over time, suggesting suboptimal efficacy or low tolerability of pregabalin for the conditions for which it is being used. The lower discontinuation rates in people that initiated on the higher capsule strengths may indicate a better risk–benefit profile, use for different indications, or use in different populations.…”
Section: Discussionsupporting
confidence: 90%
“…Following the PBS subsidy of pregabalin, we observed high rates of pregabalin initiation from 2013/14 to 2016/17 with only a slight drop in 2017/18. However, consistent with other studies, 7,17,18 we observed high rates of discontinuation which have been increasing over time, suggesting suboptimal efficacy or low tolerability of pregabalin for the conditions for which it is being used. The lower discontinuation rates in people that initiated on the higher capsule strengths may indicate a better risk–benefit profile, use for different indications, or use in different populations.…”
Section: Discussionsupporting
confidence: 90%
“…One issue not so often taken into consideration is the documentation of the treatment effect of gabapentinoids also in conditions where they are approved. One recent review of pregabalin in the management of neuropathic pain [107] concludes that pregabalin has a beneficial effect on some symptoms of neuropathic pain, but its use is associated with a number of adverse events and the overall quality of evidence supporting its use is low. The authors advocate a need for larger, robust, high-quality clinical trials with particular attention paid to minimizing selective reporting of outcomes.…”
Section: Recommendations To Healthcare Providersmentioning
confidence: 99%
“…Thus, there is insufficient evidence to make definitive statements on pregabalin's effects on QoL. 31 The capsaicin 179 mg patch is not associated with a daily pill burden, and adherence to treatment is determined by whether patients complete the intended application time. In phase III clinical trials, almost all (97-100%) of the patients completed ≥90% of the full duration of treatment (ie the patch was not removed early).…”
Section: The Capsaicin 179 Mg Patch Is Associated With a Lower Burdenmentioning
confidence: 99%